In vivo Gene Therapy to the Liver and Nervous System: Promises and Challenges - Cantore, Alessio; Fraldi, Alessandro; Meneghini, Vasco; Gritti, Angela (Frontiers in Medicine, 2022)
In vivo genetic engineering has recently shown remarkable potential as a novel effective treatment for an ever-growing number of diseases, as also witnessed by the recent marketing authorization of several in vivo gene therapy products. In vivo genetic engineering comprises both viral-vector mediated gene transfer and the more recently developed genome/epigenome editing strategies, as long as they are directly administered to patients. Here we first review the most advanced in vivo gene therapies that are commercially available or in clinical development. We then highlight the major challenges to be overcome to fully and broadly exploit in vivo gene therapies as novel medicines, discussing some of the approaches that are being taken to address them, with a focus on the nervous system and liver taken as paradigmatic examples.